2012
DOI: 10.1051/0004-6361/201118329
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of [Ne II] emission in young stars: mid-infrared and optical observations with the Very Large Telescope

Abstract: Context. The [Ne II] line 12.81 μm was proposed to be a good tracer of gas in the environments of proto-planetary disks; its origin is explained by different mechanisms: jets in outflows, photo-evaporative disk winds driven by stellar X-rays/EUV or by the X-ray irradiated proto-planetary disk atmosphere. Previous Spitzer studies gave hints toward the neon emitting mechanism by exploring correlations between the line luminosity and properties of the star-disk system. These studies concluded that the origin of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…Indeed, this line also shows two distinct components like the optical forbidden lines. Similar to the [O i] line, the HVC of the [Ne ii] is clearly associated with jets/outflows (it has been also spatially resolved toward one source; see van Boekel et al 2009), while the profile and peak velocity of the LVC are consistent with a photoevaporative disk wind driven by stellar X-ray/EUV photons (Pascucci & Sterzik 2009;Sacco et al 2012;Baldovin-Saavedra et al 2012). Thus, the [Ne ii] LVC traces either the EUV-heated or the X-ray-heated disk layer we discussed above in the context of the [O i] LVC (Meijerink et al 2008;Hollenbach & Gorti 2009;.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, this line also shows two distinct components like the optical forbidden lines. Similar to the [O i] line, the HVC of the [Ne ii] is clearly associated with jets/outflows (it has been also spatially resolved toward one source; see van Boekel et al 2009), while the profile and peak velocity of the LVC are consistent with a photoevaporative disk wind driven by stellar X-ray/EUV photons (Pascucci & Sterzik 2009;Sacco et al 2012;Baldovin-Saavedra et al 2012). Thus, the [Ne ii] LVC traces either the EUV-heated or the X-ray-heated disk layer we discussed above in the context of the [O i] LVC (Meijerink et al 2008;Hollenbach & Gorti 2009;.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, C + is not detected in IRAS 4B outflow whereas it is detected in Serpens SMM1 protostar and outflow (see Fig. 4 However, they did not detect the [Ne ii]12.8 μm line that requires fast shock velocities (Lahuis et al 2007;Baldovin-Saavedra et al 2012) or X-ray radiation (see Güdel et al 2010, for Class II disk sources).…”
Section: Comparison With Other Low-mass Protostarsmentioning
confidence: 96%
“…Thanks to the high-spectral resolution achievable with ground-based spectrographs in the mid-infrared (R ∼ 30000, or 10 km s −1 for VISIR at VLT), lines could be spectrally resolved, and the nature of the emission (disk, disk wind, or jet) for most of the objects could finally be unveiled. At the time of writing the neon line has been observed with ground-based instruments in ∼50 objects (see , Najita et al 2009, Pascucci and Sterzik 2009, van Boekel et al 2009, Sacco et al 2012, Baldovin-Saavedra et al 2012. About 50 % of the [Ne II] lines detected with Spitzer are confirmed with ground based observations.…”
Section: Atomic Tracersmentioning
confidence: 90%
“…considered FUV and X-rays in their input stellar spectrum and found that the [O I] lines are emitted from dissociation of OH with only a minor contribution from thermal emission. Recent observational studies have focused on the study of optical forbidden lines (Baldovin-Saavedra et al 2012, Rigliaco et al 2013, Manara et al 2014. Baldovin-Saavedra et al (2012) obtained UVES (VLT) high-resolution spectra for three objects with a [Ne II] line detected from the ground.…”
Section: Atomic Tracersmentioning
confidence: 99%
See 1 more Smart Citation